HUMAN CIVILIZATION BETWEEN REVELATION AND REASON - Mukran H. Usman; Azwar Azwar; Aswar Aswar (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
Human civilization can be said to be a civilization that departs from a combination of revelation and reason which is marked by the birth of various knowledge initiated by Muslim scientists. This study aims to explain that the civilization that has been achieved by humans today in various fields, such as medicine, astronomy, chemistry, politics, and economics, is the result of the ability of the human mind to explore the content of knowledge contained in divine revelation in the Qur'an. so as to produce a high civilization. This study uses a qualitative approach with library research methods and content analysis techniques. The results of the research show that the role of reason in exploring knowledge contained in divine revelation is very visible so as to produce high civilizations, especially in the fields of medicine, astronomy, chemistry, politics and economics. The implication of the research is that divine revelation contained in the Qur'an and hadith cannot be separated as a source of modern human civilization today so that returning to divine revelation in building civilization is an absolute.